Analisis Consumable Dan Biaya “Manual Cutting Oxy-Lpg” Pelat Kapal Dengan Variasi Posisi Pemotongan - Bagus Aditya; Tri Agung Kristiyono; Intan Baroroh (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2023)
Manual Cutting is part of the process in ship building and ship repair. Oxy-LPG gas is widely used in the process of cutting plates with manually or automatically method. In the process cutting of plates in ship repair, the cutting position are Down Hand, Vertical and Overhead in cause the gas consumable and cutting duration proces are still not widely known numerically. In improving the data, a survey and initial study are needed as a support, so to obtain standard data for manual plate cutting numerically, plate cutting experiments are carried out in several variations in position and plate thickness variations. The results of the equation in manual plate cutting Downhand obtained Y=43,667x-43 (Duration), Y=0.0875x-0.2833 (O2) and Y=0.051x-0.0922 (Lpg). Vertical Y=34,667x-9,333 (Duration), Y=0,1042x-0.3778 (O2) and Y=0,0608x+0,1033 (Lpg) while Overhead Y=33.667x+28,111 (Duration), 0, 0792x+0.0922 (O2) and Y=0.1008x-0.2433 (Lpg). For the cost analysis, it was found that the cost increase was 8.49% based on the function of the increase in plate thickness. If it is based on the position function, the average cost increase is 10.55%.